Small irrigation tanks as a source of malaria mosquito vectors: a study in north-central Sri Lanka - Amerasinghe, Felix P.; Konradsen, Flemming; Hoek, Wim van der; Amerasinghe, Priyanie H.; Gunawardena, J.P.W.; Fonseka, K.T.; Jayasinghe, G. (International Water Management Institute, 2001)
Thousands of small irrigation reservoirs (tanks) exist in rice ecosystems in malarious regions of south Asia. The potential of these tanks to generate malaria-transmitting mosquitoes has not been adequately evaluated. Through a study of nine small irrigation tanks in north-central Sri Lanka, this report provides an assessment of the capacity of tanks to generate malaria and nuisance mosquitoes, factors that contribute to mosquito generation, and measures that could ameliorate the problem.